Aplikasi Penerjemah Bahasa Bangka Ke Bahasa Indonesia Menggunakan Neural Machine Translation Berbasis Website - Razsiah, Fadel; Josi, Ahmat; Mubaroh, Sari (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
At this time, machine translation is one of the options for translating languages, especially for people who want to learn a language. Bangka language is a language that is often used by the Bangka people for everyday life. There have been many developments for machine translation, but no one has yet developed a translation machine for the Bangka language. The development of a machine translation using Neural Machine Translation (NMT) and its implementation using the Flask microframework is the first step for the development of a machine translation for the Bangka language. This study aims to make and find out the translation results of the Bangka language translator application into Indonesian using the RNN translator model. The development starts from creating a parallel corpus of Bangka language to Indonesian and machine translation architecture with the RNN model. The research method starts from dataset collection, data preprocessing, modeling and training, system evaluation and implementation. From the results of the BLEU Scores evaluation, a value of 55.3% was obtained for Bangka to Indonesian. Furthermore, the model is implemented in the form of a website by utilizing the Flask framework, so that users can easily translate.